2018
DOI: 10.1029/2017tc004919
|View full text |Cite
|
Sign up to set email alerts
|

Final Subduction Processes of the Paleo‐Asian Ocean in the Alxa Tectonic Belt (NW China): Constraints From Field and Chronological Data of Permian Arc‐Related Volcano‐Sedimentary Rocks

Abstract: The timing of final subduction and closure of the Paleo-Asian Ocean (PAO) is controversial.Located in a key position within the southern Central Asian Orogenic Belt, the Alxa Tectonic Belt (ATB) provides a crucial window to evaluate the final subduction processes of the PAO. This study presents field and geochronological data for Permian volcano-sedimentary rocks from the southwestern ATB. Field observations revealed a syntectonic unconformity between the Middle and Upper Permian strata. Detrital zircon U-Pb a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 110 publications
(238 reference statements)
1
39
0
Order By: Relevance
“…The conclusion is also supported by geochemical data from Carboniferous to early Permian plutons in this belt (Liu et al, 2017b; Liu, Zhao, et al, 2016; Peng et al, 2013; Shi et al, 2012; Song, Xiao, Collins, Glorie, & Han, 2018; Zheng, Zhang, & Xiao, 2019). Song, Xiao, Collins, Glorie, Han, and Li (2018) suggested that this belt probably extends eastward to the northern margin of the NCC, constituting an Andean‐type magmatic arc along the northern margin of the Alxa‐NCC during the Carboniferous to middle Permian (Liu, Zhao, et al, 2016; Zhang et al, 2007; Zhang, Zhao, Kröner, et al, 2009; Zhang, Zhao, Song, et al, 2009). The paucity of arc volcanic rocks probably results from intensive uplifting and denudation due to intraplate deformation (Darby & Ritts, 2007; Zhang et al, 2014), as documented in the Andean arcs (Ducea et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusion is also supported by geochemical data from Carboniferous to early Permian plutons in this belt (Liu et al, 2017b; Liu, Zhao, et al, 2016; Peng et al, 2013; Shi et al, 2012; Song, Xiao, Collins, Glorie, & Han, 2018; Zheng, Zhang, & Xiao, 2019). Song, Xiao, Collins, Glorie, Han, and Li (2018) suggested that this belt probably extends eastward to the northern margin of the NCC, constituting an Andean‐type magmatic arc along the northern margin of the Alxa‐NCC during the Carboniferous to middle Permian (Liu, Zhao, et al, 2016; Zhang et al, 2007; Zhang, Zhao, Kröner, et al, 2009; Zhang, Zhao, Song, et al, 2009). The paucity of arc volcanic rocks probably results from intensive uplifting and denudation due to intraplate deformation (Darby & Ritts, 2007; Zhang et al, 2014), as documented in the Andean arcs (Ducea et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors suggested an early Permian extension related to a mantle plume (Dan et al, 2015; Dan, Li, Wang, Tang, & Liu, 2014) or continental rifting (Shi et al, 2018; Zhang et al, 2012) in the northern Alxa Block, implying that the PAO has closed before the early Permian. However, many researchers proposed that there is a Carboniferous to middle Permian continental arc setting in this area (Feng et al, 2013; Liu et al, 2017a; Peng et al, 2013; Song, Xiao, Collins, Glorie, & Han, 2018; Song, Xiao, Collins, Glorie, Han, & Li, 2018; Yang et al, 2014) and argued that the PAO was not consumed until the early to middle Permian. This controversy is mainly due to non‐unique interpretations of isotopic and geochemical analyses of the Carboniferous to early Permian plutonic rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Structural style and regional tectonic setting of the Hailar Basin. [Colour figure can be viewed at wileyonlinelibrary.com] 6 | TECTONIC IMPLICATIONS Late Permian orogenic activity has been well documented and was attributed to the closure of the Palaeo-Asian Ocean (Li, 2006;Meng, 2003;Miao et al, 2008;Paul et al, 2014;Song et al, 2018;Xiao et al, 2018). The resulting thrust faults can be also observed on the seismic section (Figure 8).…”
Section: Figure 13mentioning
confidence: 99%
“…Located in a key position in the southern CAOB, the Alxa Tectonic Belt (ATB; Song et al, ; Song, Xiao, et al, ) connects the Tianshan and Beishan orogenic belts to the west with the Inner Mongolia orogenic belt to the east (Figure b). The tectonic evolution of the ATB during the Palaeozoic is essential for understanding the overall subduction–accretion history of the southern CAOB.…”
Section: Introductionmentioning
confidence: 99%
“…However, the geodynamic setting of the ATB during the late Palaeozoic, especially the late Carboniferous–early Permian, is highly controversial. For example, based on the studies of late Palaeozoic ophiolitic mélanges, ultramafic–mafic complexes, granitic plutons, and volcano‐sedimentary rocks, an accretionary environment ascribed to the southward subduction (present coordinates) of the PAO was proposed to have existed in the ATB during the late Carboniferous to early Permian (Liu et al, , ; Zhang et al, ; Zheng et al, ; Zheng et al, ), or even late Permian (Feng et al, ; Song, Xiao, et al, ). In contrast, Dan, Li, Wang, Tang, and Liu () insisted that the ATB was in a mantle plume‐related extensional setting after the ocean had closed before the late Carboniferous.…”
Section: Introductionmentioning
confidence: 99%